15. The effect of cannabinoids on the stretch reflex in multiple sclerosis spasticity. Issue 12 (December 2016) - Marinelli, L.; Mori, L.; Canneva, S.; Colombano, F.; Currà, A.; Fattapposta, F.; Bandini, F.; Capello, E.; Abbruzzese, G.; Trompetto, C.
Abstract : The aim of this observational study was to assess the efficacy of tetrahydrocannabinol-cannabidiol oromucosal spray (THC:CBD, Sativex) on spasticity using the stretch reflex in subjects with multiple sclerosis (MS). Numeric rating scale (NRS) for spasticity, modified Ashworth scale (MAS) and the stretch reflex were assessed before and during treatment in 57 MS patients with spasticity eligible for THC:CBD treatment. A significant reduction of stretch reflex amplitude, as well as significant reductions of NRS and MAS scores were observed. There was a low concordance between the three measures (stretch reflex, NRS and MAS), likely related to the different aspects of muscle hypertonia assessed. Stretch reflex responders were taking a significantly higher number of puffs, while no differences were found in the responders by the other scales, suggesting that higher dosage would add benefit if tolerated. The present study confirms the efficacy of cannabinoids in reducing spasticity in patients with MS, suggesting a higher sensitivity and specificity of the stretch reflex compared to other measures. As an objective and quantitative measure of spasticity, the stretch reflex is particularly useful to assess the effects of cannabinoids on spinal excitability and may have a role in future pharmacological studies.